Sensores de Bragg funcionalizados com óxido de grafeno - Matos, Yuri Bilk (2020)
In the last years, Fiber Bragg gratins (FBGs) have been widelly studied, both in industry and universities. some of it's main topics of research are: improvement of the sensor's sensibility, and how to modulate the sensor's signal to detect the presence of some analyte of interest. It is possible that we may contribute to both topics by incorporating graphene oxide (GO) technology to FBGs. GO is a 2D nanomaterial, made by hexagonally structured carbon sheets, with oxygen functional groups. In terms of sensibility, it is possible that a GO coating might increase the FBG response. In terms of detecting analytes, GO may be used as a plataform where we can graft chemical functions capable of interacting with the molecules we wish to detect. In this research, we study the synthesis of GO through a modified Hummers' method, and a depositiong technique to coat FBGs with GO, by using (3-Aminopropyl)triethoxysilane (APTES) as a bonding substance between sensor and coating. The research was done in three steps. First, we synthetized two samples of GO, by two different modifications in the traditional Hummers' method. These samples were characterized by means of transmission electron microscopy, Raman spectroscopy, and refraction index. Through the microscopies, we were able to identify zones of GO layer superposition and folding. From the Raman spectroscopy, it was possible to extract data about the material's chemical-physical properties, by deconvoluting the materials's spectra and identifying the resulting peaks. In the second setp, FBGs were produced by laser engraving.  The FBGs were subsequently corroded, and its response to variations in the refractive index of surrounding media was measured. In the third step, the FBGs were coated with the GO, and characterized by scanning electron microscopy, Raman spectroscopy, and profilometry. The results shown that the coating was succesfull, yet heterogeneous. The response of the coated FBGs was also measured, and an improvement of the sensor's sensibility was detected.